Nutrient dynamics and oceanographic features in the central Namibian upwelling region as reflected in δ15N-signals of suspended matter and surface sediments - S. Meisel; U. Struck; K.-C. Emeis (Fossil Record, 2011)
The study deals with the modern situation of the northern Benguela Upwelling, directing particular attention to the shelf region off central Namibia (21 to 24° S). At the centre of the investigation is the comparison of δ15N-records in surface sediments (δ15Nsediment) with suspended particulate matter (δ15NSPM) from the surface ocean. In addition to that, water column profiles (including hydrographic data) provide an insight into changes of δ15NSPM with depth and elucidate potential offsets between δ15NSPM and δ15Nsediment. The parallel spatial trend of δ15Nsediment and surface ocean δ15NSPM shows that secondary processes are not so pronounced as to obliterate the signal generated in the surface waters. Highest δ15N-signatures are found right off the coast where water temperatures are lowest. Concomitantly high productivity rates and low bottom oxygen suggest the upwelling of denitrified source waters. With increasing distance offshore, δ15N declines unexpectedly, reaching a minimum above the shelf break. Beyond that, the trend reverses to "normal" with δ15N-signals continuously increasing towards the mesopelagic ocean. The decrease in δ15Nsediment and surface ocean δ15NSPM with increasing distance to the coast disagrees with the concept of Rayleigh fractionation kinetics, viz. the progressive 15N-enrichment of the nitrate pool as it is gradually used up by phytoplankton growth. On the basis of the available evidence, the downward trend of δ15N results from decreased relative nitrate consumption, resting on a combination of reduced primary production and the existence of an ulterior source of nutrients. Nutrient replenishment seems to occur via an additional upwelling front at the edge of the shelf as well as tapping of subsurface nitrate through sufficiently deep penetration of wind- and wave-induced mixing over large areas of the shelf. Both mechanisms are considered capable of working against the expected nutrient drawdown (i.e. 15N-enrichment) as surface waters travel offshore. It is important to keep these caveats in mind when interpreting δ15N-variations in sediment cores retrieved from this area. doi:10.1002/mmng.201100005